2019
DOI: 10.1155/2019/5763658
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Age-Related Eye Diseases

Abstract: Background. Autophagy is a catabolic process that depends on the lysosome. It is usually used to maintain cellular homeostasis, survival and development by degrading abnormal substances and dysfunctional organelles, especially when the cell is exposed to starvation or other stresses. Increasing studies have reported that autophagy is associated with various eye diseases, of which aging is one of the important factors. Objective. To summarize the functional and regulatory role of autophagy in ocular diseases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 130 publications
0
28
0
Order By: Relevance
“…Autophagy is an intracellular recycling process that regulates cellular homeostasis, such as RPE cells [38,47]. However, the autophagy activity was decreased in the AMD disease, which is caused by the oxidative damage originating from the dysfunction of RPE cells [21]. Therefore, the study tried to use quercetin, a potential antioxidant substrate, to investigate the protective efficacy on the mice with retinal oxidative damage, and demonstrated the detailed mechanism in the ARPE19 cell line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is an intracellular recycling process that regulates cellular homeostasis, such as RPE cells [38,47]. However, the autophagy activity was decreased in the AMD disease, which is caused by the oxidative damage originating from the dysfunction of RPE cells [21]. Therefore, the study tried to use quercetin, a potential antioxidant substrate, to investigate the protective efficacy on the mice with retinal oxidative damage, and demonstrated the detailed mechanism in the ARPE19 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ROS generation can induce autophagy [18,19]. Autophagy has been reported to be involved in the oxidative responses of age-related eye diseases [21]. An increased level of oxidative stress has been shown to contribute to various autophagy-associated proteins, such as Beclin-1, Bcl-2, LC3B, and p62 [38,42].…”
Section: Quercetin Influenced the Expression Of Autophagic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, an impairment of autophagy due to oxidative stress is related with several age-related eye diseases such as dry eye diseases, corneal dystrophy type 2, cataracts and retinal dystrophies like AMD, glaucoma, DR, and retinal artery occlusion [51,52].…”
Section: Autophagy and Oxidative Stressmentioning
confidence: 99%
“…Impairment of autophagy has been shown to contribute to many diseases [27]. Autophagy has both positive and negative effects on the progress of AMD [28]. Autophagy can be modulated by UVA in the skin [29,30], but whether UVA leads to AMD through regulating autophagy processes in RPE cells has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%